Exploring Waqf Based Takaful Fund As Financial Aid For B40 Group In Malaysia - Mohamad Zaharuddin Zakaria; Ahmad Zaki Salleh; Mushaddad Hasbullah; Abdul Manan Ismail; Mohd Afiq Ab Jalil (IIUM PRESS, 2024)
Non-Indexed Publication